Assessment of business resilience abilities: the case of industry and commerce of Santa Maria – RS - Soares, Matheus Pedroso Valau; Soliman, Marlon (Revista de Administração da UFSM, 2024)
Purpose: This research aimed to evaluate the potential for resilient performance in the face of crises and adversities for companies located in the city of Santa Maria – RS (Brazil). Design/methodology/approach: We adopted a quantitative approach. The research was carried out through five sequential steps: (i) construction and validation of the research instrument; (ii) definition of the sample size and sampling procedures; (iii) data collection; (iv) data analysis and interpretation of results; and (v) elaboration of recommendations. A research instrument containing 44 questions was built and distributed among potential respondents, obtaining 87 valid answers, which corresponds to a statistically representative sample for the parameters adopted. Findings: Our sample was divided into two subsets, representing the Industrial and Commerce sectors. Resilience assessment accounted for four dimensions: the ability to respond, to anticipate, to monitor, and to learn. Results for both sectors showed scores ranging from 3.4 to 3.7 (out of 5) in the four dimensions evaluated. This reveals both sectors have been developing practices that positively contribute to the improvement of resilience, although there are opportunities for improvement. Originality/value: This research sheds light on the resilience ability of the cases surveyed, enabling managers to take action to strengthen their organizations and overcome crises and adversities. Additionally, our findings demonstrate how resilience abilities can be assessed, considering the scope of an economic sector and a geographical area. This approach can be adopted by researchers, policymakers, and development agencies to assess the resilience abilities of firms within their sphere of influence.